2011
DOI: 10.1002/ptr.3696
|View full text |Cite
|
Sign up to set email alerts
|

Liquiritigenin Inhibits Serum‐induced HIF‐1α and VEGF Expression via the AKT/mTOR‐p70S6K Signalling Pathway in HeLa Cells

Abstract: Liquiritigenin (LQ) is a non-toxic dietary flavonoid with chemopreventive and anticancer properties. However, the mechanism of its antiangiogenesis remains unclear. Hypoxia-inducible factor-1α (HIF-1α) and its downstream target, vascular endothelial growth factor (VEGF), play a critical role in tumour angiogenesis and represent an attractive chemotherapeutic target. In this study, we investigated the effect of LQ on the molecular mechanism of angiogenesis. We found that LQ inhibited VEGF expression at both mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Inhibition of mTOR has also been implicated to be involved in resveratrol-mediated inhibition of glucose metabolism in cancer cells (16,18). Furthermore, a recent study observed that liquiritigenin inhibited HIF-1a accumulation in HeLa cells by modulating Akt and mTOR signaling (32). Our study corroborates these reports by suggesting that PI3K/Akt and mTOR signaling may be involved in the capacity of resveratrol to suppress cancer cell glucose uptake.…”
Section: Discussionsupporting
confidence: 88%
“…Inhibition of mTOR has also been implicated to be involved in resveratrol-mediated inhibition of glucose metabolism in cancer cells (16,18). Furthermore, a recent study observed that liquiritigenin inhibited HIF-1a accumulation in HeLa cells by modulating Akt and mTOR signaling (32). Our study corroborates these reports by suggesting that PI3K/Akt and mTOR signaling may be involved in the capacity of resveratrol to suppress cancer cell glucose uptake.…”
Section: Discussionsupporting
confidence: 88%
“…Although the treatment of human cervical cancer cells (positive for HPV16 or HPV18) with widespread dietary flavanones including fruit flavonoids hesperetin, naringenin and naringin can lead to a dose-and timedependent inhibition of proliferation (see Table 2), this activity reveals only at rather high concentrations (usually more than 100μM) and there are no cytotoxic effects on the cell viability at lower doses (Virgili et al, 2004;Kanno et al, 2005;Liu et al, 2011;Kim et al, 2012;Xie SR et al, 2012;Alshatwi et al, 2013;Ramesh and Alshatwi, 2013;Deng et al, 2014). This anticancer action occurs through induction of cell cycle arrest and promotion of apoptosis.…”
Section: Flavanonesmentioning
confidence: 99%
“…This anticancer action occurs through induction of cell cycle arrest and promotion of apoptosis. Moreover, liquiritigenin is also able to inhibit the expression of vascular endothelial growth factor (VEGF) and interfere with tumor angiogenesis, thereby suppressing the progression of cervical cancer Xie SR et al, 2012).…”
Section: Flavanonesmentioning
confidence: 99%
“…Decreased expression of HIF-1α is associated with slower cell growth and tumor angiogenesis (12,31). HIF-1α and VEGF-A expression are strongly associated with cancer progression and angiogenesis (12)(13)(14). In our study, the control group demonstrated marked expression of p-mTOR, which is the activated form of mTOR and its downstream protein, HIF-1α and VEGF-A, while the high and low-dose aspirin and everolimus groups effectively inhibited the expression of p-mTOR, HIF-1α and VEGF-A.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor tissue is usually accompanied by hypoxia, which promotes HIF-1α production. HIF-1α and its downstream target, VEGF-A, play critical roles in tumor angiogenesis and represent an attractive chemotherapeutic target (11)(12)(13). Ruan et al revealed that the phosphatidylinositol 3-kinase (PI3K)/AKT/mTOR signaling pathway as 'the regulation center of angiogenesis' could regulate the expression of VEGF-A by hypoxia and HIF-1α, cancer genes, hormones, growth factors and cytokines and other factors (14).…”
Section: Introductionmentioning
confidence: 99%